Membangun Jiwa Wirausaha Untuk Menghadapi Dunia Kerja Dan Menciptakan Peluang Usaha Bagi Siswa Sekolah Menengah Kejuruan - Febri Yoga Sapta Raharjo; Yuniarti Herwinarni; Juli Riyanto Wijaya (CV. Multi Kreasi Media, 2025)
This community service activity aims to provide education on the fundamental concepts of entrepreneurship, business opportunities in the digital era, strategies for starting a business at an early stage, and an introduction to financial reporting in small and medium enterprises for students at SMK NU 1Islamiyah Kramat, Tegal Regency. Through a participatory approach, it is expected that students will be motivated to explore their business potential and be better prepared to face the workforce or engage in entrepreneurship. This activity was attended by 100 participants and employed methods such as interactive lectures, discussions, and Q&A sessions, along with an evaluation using pre-test and post-test questionnaires. The results of this activity indicate that students have a high interest in the field of entrepreneurship and have gained a better understanding of basic entrepreneurial concepts and business opportunities. This community service initiative is expected to serve as a step towards fostering an entrepreneurial mindset among students, equipping them with a higher level of readiness to enter the workforce and create their own business opportunities.